Analisis strategi diversifikasi Bank Syariah Indonesia: Studi kasus pengembangan produk syariah untuk menjangkau segmen pasar baru - Aisyah, Dwi Danty (Maliki Interdisciplinary Journal, 2024)
Product diversification strategy implemented by Bank Syariah Indonesia (BSI) in an effort to reach new market segments. As the largest Islamic bank in Indonesia, BSI faces the challenge of expanding its market share amidst the dominance of conventional banking and low Islamic financial literacy among the public. This article highlights the diversification strategy implemented by BSI through the development of digital financial products, microfinance for SMEs, Islamic investment, and environmentally friendly products. The results of the analysis show that this diversification strategy has contributed positively to the growth of BSI's assets and net profit, while increasing Islamic financial inclusion in Indonesia. However, challenges such as low Islamic financial literacy and competition with conventional banks still need to be overcome. This study concludes that product diversification is the key to BSI's success in expanding its market reach, but innovation and public education remain important aspects that must be strengthened in the future.